2016
DOI: 10.4103/1305-7456.195178
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education on oral health students’ attitudes in Australia and New Zealand

Abstract: Objective:The aim of this study was to evaluate the oral health attitudes and behavior of students in the oral health curriculum in Australia and New Zealand.Materials and Methods:The Hiroshima University - Dental Behavioral Inventory was administered to students in the first (year 1) and final years (year 3) of the oral health curriculum at Charles Sturt University in Australia and the University of Otago in New Zealand. A total of fifty-two year 1 students and forty-five year 3 students completed English ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Scientific studies have showed that individuals with a higher dental specific education achieve better scores for HUDBI, and therefore, the need for specific education with respect to oral health-related practices should be emphasized, both in the dental practice and as a general public oral health policy. 63 65 …”
Section: Discussionmentioning
confidence: 99%
“…Scientific studies have showed that individuals with a higher dental specific education achieve better scores for HUDBI, and therefore, the need for specific education with respect to oral health-related practices should be emphasized, both in the dental practice and as a general public oral health policy. 63 65 …”
Section: Discussionmentioning
confidence: 99%
“…However, though senior medical students did consume less soft drinks than their junior counterparts, the difference in the number of beverages consumed was not statistically significant. Because students in their clinical clerkships educate and counsel their patients on various health promotion behaviors, including nutrition counseling, it is expected that as the academic year advances, students become more self-aware about their own deleterious attitudes to health [ 14 ]. A study done in India showed that final-year medical students had a significantly higher score for oral health knowledge, attitude, and behavior than first-year medical students (p<0.01) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Knowledge of the importance of oral health and risk factors for development of oral diseases may have a strong effect on one's behavior and attitudes, with students being the perfect target group since theirs is the very age when most of the behavior and attitudes are defined. [14][15][16][17] It is feasible that students in healthcare sector will have greater scope of knowledge on health issues, since their very choice of future profession means that they are aware of the importance of not only human health, but also the need to participate actively in providing help to others.…”
Section: Introductionmentioning
confidence: 99%